Jüngste Änderungen im gewerblichen Rechtsschutz in Japan - Beyerlein, Thorsten (Zeitschrift für Japanisches Recht, 2007)
utility model, design, and trademark law. This article deals with the major amendments and highlights their consequences for IP owners. In particular, the time frame for patent applications has been extended, and the possibilities for amendments on patent applications during the examination proceedings have been modified. New legal definitions with respect to the export and possession of counterfeiting products have been introduced. Design protection has been extended to 20 years from the date of registration, and various other amendments have to be considered with respect to similarity and the scope of design protection. Under the amended trademark law, trademarks used by retailers may now be registered as service marks. Furthermore, the range of legal entities with the right to register collective trademarks has been enlarged. Last but not least, criminal penalties for IP infringement have become more rigorous.